Improving Students’ Creative Thinking and Achievement through The Implementation of Multiple Intelligence Approach with Mind Mapping - I Wayan Widiana; I Nyoman Jampel (Institute of Advanced Engineering and Science, 2016)
This classroom action research aimed to improve the students’ creative thinking and achievement in learning science. It conducted through the implementation of multiple intelligences with mind mapping approach and describing the students’ responses. The subjects of this research were the fifth grade students of SD 8 Tianyar Barat, Kubu, and Karangasam. The objects of this research were multiple intelligence, achievement in science and students’ response. The research was conducted in two cycles and every cycle consisted of planning, action implementation, observation, and reflection. The data of students’ creative thinking were collected by performance test; the data of students’ achievement in learning science were collected through questionnaire. After the data were collected, then they were analyzed descriptively and quantitatively. The results of the study showed that (1) the implementation of multiple intelligence approach improved the students’ creative thinking and achievement in learning science. The improvement in the students’ creative thinking from cycle I to cycle II is 16.56%. (2) The improvement of the students’ achievement in learning science from cycle I to cycle II is 11.46%. (3) The students’ response to the implementation of multiple intelligence with mind mapping fell into category positive.The students felt happy in learning science through the implementation of multiple intelligences with mind mapping.